POWER STRUCTURES AND SOCIAL DYNAMICS IN BAQIR’S BEYOND THE FIELDS: A CULTURAL STUDY IN BOURDIEU’S PERSPECTIVE (Contemporary Journal of Social Science Review, 2024)
This research investigates the cultural experiences of people living in Pakistani society. This study aims to examine “Beyond the Fields” (2019) by Aysha Baqir using the lens of practice theory by Pierre Bourdieu in cultural studies and, this research probs to uncover the complex structures and social dynamics molding individual practices in the context of post-colonial Pakistan. The protagonist of the novel Zara, traverses social constraints, & the narrative illustrates cultural practices, power struggles, and inequalities. Within South Asia’s sociocultural context, the current study delves into the complex discursive practices and power dynamics that have maintained gender-based oppression. Bourdieu’s concepts of habitus, structures, practices, symbolic power, doxa, orthodoxy, heterodoxy, and social reproduction are involved in the theoretical framework. Bourdieu’s theoretical framework provides a lens through which we discern how habitus is formed unconsciously from our surroundings, and how power dynamics and gender inequalities are part of the external structures. It is examined through different characters how the novel “Beyond the Fields” depicts the intricate social structures contributing to differences in individual practices. Protagonist Zara’s journey from establishing her habitus due to society’s structures is the main part of the investigation. Key concepts of Bourdieu escort the analysis, addressing emancipation social change & reproduction of the structures. This research’s significance lies in enhancing readers’ comprehension of Pakistani literature and carrying it out as a source for further study.